2020
DOI: 10.1242/dev.189183
|View full text |Cite
|
Sign up to set email alerts
|

A mutation affecting laminin alpha 5 polymerisation gives rise to a syndromic developmental disorder

Abstract: Laminin alpha 5 (LAMA5) is a member of a large family of proteins which trimerize and then polymerise to form a central component of all basement membranes. Consequently, the protein plays an instrumental role in shaping the normal development of the kidney, skin, neural tube, lung, limb and many other organs and tissues. Pathogenic mutations in some laminins have been shown to cause a range of largely syndromic conditions affecting the competency of the basement membranes to which they contribute. We report t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 48 publications
3
36
0
Order By: Relevance
“…In addition, laminin-511 is involved in mouse and human hair follicle morphogenesis by a mechanism supporting dermal hair papilla development and hair growth [151,152]. A mutation in the polymerization domain of the laminin α5 chain was recently identified in a patient with a complex developmental disorder affecting multiple organ systems [153]. A mouse model recapitulating this mutation revealed that the variant laminin is trimerized and secreted, suggesting that its failure to polymerize does not impede its incorporation into basement membranes [153].…”
Section: The Archetypal Laminin/collagen IV Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, laminin-511 is involved in mouse and human hair follicle morphogenesis by a mechanism supporting dermal hair papilla development and hair growth [151,152]. A mutation in the polymerization domain of the laminin α5 chain was recently identified in a patient with a complex developmental disorder affecting multiple organ systems [153]. A mouse model recapitulating this mutation revealed that the variant laminin is trimerized and secreted, suggesting that its failure to polymerize does not impede its incorporation into basement membranes [153].…”
Section: The Archetypal Laminin/collagen IV Networkmentioning
confidence: 99%
“…A mutation in the polymerization domain of the laminin α5 chain was recently identified in a patient with a complex developmental disorder affecting multiple organ systems [153]. A mouse model recapitulating this mutation revealed that the variant laminin is trimerized and secreted, suggesting that its failure to polymerize does not impede its incorporation into basement membranes [153]. However, no major skin defects were reported, and future studies will need to uncover the molecular status of the DEJ.…”
Section: The Archetypal Laminin/collagen IV Networkmentioning
confidence: 99%
“…Reportedly, Lama5 is one type of the laminin proteins, which are composed of alpha, beta and gamma chains and act as the major components of basement membranes [22]. Lama5 is located in cell nucleus and is broadly expressed in lung, kidney, skin, neural tube, limb and many other tissues and organs [23].…”
Section: Resultsmentioning
confidence: 99%
“…Consistent with this hypothesis, much of the UbCLaNt::R26CreERT2 mice phenotypes resemble those from mice where LM networks cannot form due either to LN domain mutations or overexpression of the LM-network disrupting protein, netrin-4. Specifically, mice with a mutation in the LN domain of LM α5 die before birth exhibiting defective lung development and vascular abnormalities in the kidneys 68 . While mice with LM β2 LN domain mutations or LN domain deletions exhibit renal defects, and although viable at birth, become progressively weaker and die between postnatal day 15 and 30 6974 .…”
Section: Discussionmentioning
confidence: 99%
“…This study provides the first in vivo evidence that LaNt α31, the newest member of the LM superfamily, is a biologically relevant matricellular protein and emphasises the importance of α LN domains as regulators of tissue homeostasis. Indeed, whereas identification of α LN domain mutations in rare inherited disorders have established that LN domains matter 19, 22, 9395 , the LaNt α31 protein is a naturally occurring splice isoform 25 which suggests active regulation of the LN domain interactions via alternative splicing. Changes to alternative splicing rates often occur in normal situations, including during development and tissue remodelling, in response to damage such as in wound repair, and can be dysregulated in pathological situations including frequently in cancer 9698 Considered in this way, the finding the LaNt α31 is biologically active in vivo has exciting and far-reaching implications for our understanding of BM biology.…”
Section: Discussionmentioning
confidence: 99%